Decreased thermal conductivity in Bi2Sr2Co2Ox bulk materials prepared by partial melting. Issue 9 (18th April 2016) - Combe, Emmanuel; Funahashi, Ryoji; Barbier, Tristan; Azough, Feridoon; Freer, Robert
Abstract: Abstract : Bi2 Sr2 Co2 O x (BSC-222) bulk materials have been prepared in air by single hot pressing or partial melting followed by hot pressing. Thermal transport properties of as-prepared samples were compared with BSC-222 samples prepared by single partial melting. Samples prepared through hot pressing have a high bulk density and improved preferential grain orientation. Bulk density and preferential grain orientation are significantly better in samples processed by partial melting followed by hot pressing. In samples prepared by partial melting, the presence of sub-micrometer-sized secondary phases Bi0.75 Sr0.25 O x, Sr-based oxide, and CoO, is observed. The lattice contribution to the total thermal conductivity decreases significantly in partially melted BSC-222 samples. By using a classical phonon transport model, this result demonstrates that the decrease in lattice thermal conductivity in partially melted BSC-222 samples may be linked not only to porosity but also to the presence of defects, induced by partial melting process, which may play an important role in phonon scattering.